UPAYA PEMERINTAH DESA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT MELALUI BADAN USAHA MILIK DESA: Studi Kasus: Desa Sidoharjo Kecamatan Gedeg Kabupaten Mojokerto - Prasetya Dinda Lesmana, Arry; Muhaimin, Hikmah; Yudha Utama, Jenny (MAJAPAHIT POLICY, 2023)
The Village Law provides an opportunity for the Village Government to be independent in managing all its potentialis in its administrative area. Of course, community involvement is needed to be able to manage existing potential. In this research aimsto find out the Village Government's Efforts to Improve Community Welfare through Sidoharjo Village-Owned Enterprises, DistrictGedeg, Mojokerto Regency. In order to find out the efforts made by the village government, researchers used the theoretical concept of Edi Suhartoregarding Welfare using several indicators including the fulfillment of physical, spiritual and social needs, then Institutionsor Institutions which of course have a role in this research, the next indicator is the activities or activities carried out withininstitutions within the Village Government related to this research, this research uses qualitative research methods with this type of researchdescriptive analysis to describe the Village Government's efforts to improve community welfare through state-owned enterprisesVillage. The results of this research show that the Village Government and Village-owned Enterprises have made various efforts toTo improve community welfare, the efforts made are by developing Village-Owned Enterprise business units and effortsto increase community enthusiasm in developing these business units, which of course requires developmentthe role of various aspects and requires strong synergy so that this goal can be achieved. However, for now, efforts are still being madehas not had a broad impact on society